1994
DOI: 10.1021/jm00051a011
|View full text |Cite
|
Sign up to set email alerts
|

1-(2,5-Dimethoxy-4-(trifluoromethyl)phenyl)-2-aminopropane: A Potent Serotonin 5-HT2A/2C Agonist

Abstract: A method was found to synthesize 1-(2,5-dimethoxy-4-(trifluoromethyl) phenyl)-2-aminopropane, 5, and its des-alpha-methyl congener 2-(2,5-dimethoxy-4-(trifluoromethyl)phenyl)aminoethane, 6, the trifluoromethyl analogs of substituted hallucinogenic phenethylamine derivatives such as 1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane (3, DOI) that are potent 5-HT2A/2C agonists. In our hands, 5 and 6 have proven to have affinity for [3H]ketanserin or [125I]-3-labeled 5-HT2A/2C sites in rat cortex comparable to or high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
0
3

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 9 publications
5
73
0
3
Order By: Relevance
“…However, using the same SPA approach as employed herein, DOI robustly activated 5-HT 2A receptors coupled to Gq expressed in CHO cells (Cussac et al, 2002a). Further, by analogy to the present work, DOI also exhibited submaximal efficacy as compared to 5-HT in stimulating PI turnover in NIH-3T3 cells (Nichols et al, 1994). Thus, the precise degree of 5-HT 2A receptor stimulation by DOI depends upon the experimental procedure employed.…”
Section: Discussion Evidence For Activation Of Gq/11 By 5-ht Doi Andsupporting
confidence: 63%
“…However, using the same SPA approach as employed herein, DOI robustly activated 5-HT 2A receptors coupled to Gq expressed in CHO cells (Cussac et al, 2002a). Further, by analogy to the present work, DOI also exhibited submaximal efficacy as compared to 5-HT in stimulating PI turnover in NIH-3T3 cells (Nichols et al, 1994). Thus, the precise degree of 5-HT 2A receptor stimulation by DOI depends upon the experimental procedure employed.…”
Section: Discussion Evidence For Activation Of Gq/11 By 5-ht Doi Andsupporting
confidence: 63%
“…Our results extend earlier observations on the pharmacology of phenylisopropylamine derivatives, and they also provide for the first time a relative assessment of their ␣-demethylated phenethylamine congeners acting upon the PLA 2 -mediated signal transduction pathway. Previous data have shown that ␣-methylation of phenethylamines causes an increase in drug efficacy for the 5-HT 2A/2C PLC-IP response, which could be associated with the higher hallucinogenic potency of phenylisopropylamines compared with the corresponding phenethylamines (Nichols et al, 1994). In a recent report, the Nichols group showed that some phenylisopropylamines have higher intrinsic activities than their phenethylamine analogs regarding the PLC-IP effector route coupled to the 5-HT 2A receptor (Parrish et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Among the best known are 2,5-dimethoxy-4-iodophenethylamine (2C-I), 2,5-dimethoxy-4-bromophenethylamine (2C-B), and 2,5-dimethoxy-4-methylphenethylamine (2C-D), the ␣-demethylated analogs of DOI, DOB, and DOM, respectively. The data available for these phenethylamines show that their affinities for 5-HT 2A receptors are similar to those of their phenylisopropylamine counterparts, whereas different functional models have shown that their efficacies are lower than those of their ␣-methylated analogs (Glennon et al, 1992;Nichols et al, 1994;Acuñ a-Castillo et al, 2002;Parrish et al, 2005). Again, with few exceptions, most in vitro studies on these compounds examined only PLC-mediated responses.…”
mentioning
confidence: 99%
“…A pharmacological mechanism also contributes to the difference in potencies; the a-methyl group increases activity at 5-HT 2A receptors while having no effect at 5-HT 2C sites. [151] Comparison of phenethylamines with their (AE )-phenylisopropylamine counterparts clearly demonstrated similar binding affinities yet significant differences in their ability to activate second messenger systems. [152] Higher a-alkyl homologues of phenylalkylamines, or a-dialkyl substituted analogues showed little or no activity.…”
Section: Classic Phenylalkylaminesmentioning
confidence: 97%
“…[150] Similarly, the binding affinity of compound 18 (DOTFM, K i = 1.5 nm) was close to that of its phenethylamine congener (K i = 1.1 nm). [151] A number of hypotheses account for the discrepancy between the binding affinities and in vivo potency of these compounds. The a-methyl group may increase the general lipophilicity of the molecule, enhancing CNS distribution.…”
Section: Classic Phenylalkylaminesmentioning
confidence: 99%